CO 13 - A FERRIC CARBOXYMALTOSE PROTOCOL IN ANAEMIC PATIENTS FOR POSTBARIATRIC SURGERY: A RETROSPECTIVE COHORT ANALYSIS - Castro, Ana; Afonso, Diana; Silva, Emilia; Velha, Sara; Viegas, Beatriz (Journal of the Portuguese Society of Anesthesiology, 2023)
x